Analysis of Slope Stability on Subulussalam - Lipat Kajang Road - Yunita, Halida; Sungkar, Munira; Akmal, Abdiel Khaleil; Ardika, Jumelia (Graduate School of Universitas Syiah Kuala, 2023)
Landslides frequently occur on the Subulussalam Lipat Kajang road segment as a result of heavy rain that lasts for a long time. In addition to landslides, the Subulussalam area is vulnerable to earthquakes because it was once the site of a tectonic earthquake with a magnitude of 6.7 on the Richter scale. The extent of the destruction, as well as the number of victims, was caused by a lack of emergency planning. This research aims to see if the slope conditions are safe when subjected to an earthquake load and if appropriate handling methods can be found based on the soil characteristics at the research site. The slope is considered dangerous after being given an earthquake load of 1.044; according to the results of the safety factor value in the existing condition, sheet pile strengthening is required. The slope has been reinforced with sheet piles and is now in a safe state of 1,940.